БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ КОММУНИКАТИВ-НУТҚ МАДАНИЯТИНИ РИВОЖЛАНТИРИШ ИМКОНИЯТЛАРИ - Содиқов, Ҳ.М.; Содиқова, Д.Р. (SCIENCE and SOCIETY, 2021)
This article considers the use of texts of artistic and ethical content for the development of communicative-speech culture of the future teacher, which is interpreted as a synthesis of knowledge and experience in the field of pedagogy, in terms of achieving the ultimate goal in the training of future teachers.